A comparison of optophysiological biomarkers of photoreceptor stress and phototoxicity in BALB/cJ, B6(Cg)-Tyrc-2J/J, and C57Bl/6J mouse strains - Bell, Brent A.; Kaul, Charles; Dunaief, Joshua L.; Hollyfield, Joe G.; Bonilha, Vera L. (Frontiers in Ophthalmology, 2023)
Confocal scanning laser ophthalmoscopy and spectral-domain optical coherence tomography have been used by vision researchers for more than two decades to evaluate the eyes from numerous animal species. These instruments were used in this study to obtain imaging data sequentially from the retinas of three widely used experimental mouse strains to document changes induced by two contrasting vivarium lighting conditions. Mice included BALB/cJ, B6(Cg)-Tyrc-2J/J and C57Bl/6J which were reared under dim light until ~9 weeks of age. At this time, they underwent baseline imaging and were either returned to the dim light room or relocated to the top rack cage position in a standard vivarium. Mice were then followed for several months by ocular imaging to catalog the retinal dynamics as a function of dim vs. elevated top rack lighting conditions. Following exposure to elevated light conditions, B6(Cg)-Tyrc-2J/J underwent similar changes as BALB/cJ in regards to photoreceptor outer segment shortening, photoreceptor layer proximal aspect hyperreflective changes, and the development of retinal infoldings and autofluorescent sub-retinal inflammatory monocytes. Infoldings and monocytes developed at a slower rate of progression in B6(Cg)-Tyrc-2J/J vs. BALB/cJ. The photoreceptor outer nuclear layer thickness of BALB/cJ degenerated at a steady rate from elevated light onset in contrast to B6(Cg)-Tyrc-2J/J, which were unremarkable for many weeks before collapsing once infoldings and monocytes plateaued. Changes in C57Bl/6J mice were unremarkable for all imaging biomarkers assessed with exception to monocytes, which showed significant accumulation in elevated vs. dim light exposed mice following ~1 year of observation. These data were evaluated using Spearman’s correlation and Predictive Power Score matrices to determine the best imaging biomarkers for indicating vivarium light stress and light-induced photoreceptor degeneration. This study suggests that changes in proximal aspect hyperreflectivity, outer segment shortening, retinal infoldings and monocyte recruitment are all excellent indicators of light stress and light-induced degeneration in albino B6(Cg)-Tyrc-2J/J and BALB/cJ mouse strains. Whether these indicators are translatable and applicable to human diseases is yet to be determined, however, prior clinical imaging results in humans and other animal models are supportive of these results observed in laboratory mice.